2019
DOI: 10.1088/1757-899x/572/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Visible light wireless data communication in industrial environments

Abstract: Significant implementations and encouraging results have already been achieved using visible light communication (VLC) technology for different applications from indoor to free space optics (FSO) and even underwater communication. The LED light fixtures are about to be used with dual functionality - illumination and fast wireless data communication - and when the technology will become mature enough, the general costs for both will considerably decrease. However, especially due to a complex multipath channel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The main challenge is light's limited coverage, primarily when implemented in large warehouses with high ceilings [256]. Also, the pollution existing in industrial environments can degrade the performance of VLC systems [257]. The industrial VLC-based solutions reported in the literature are limited compared to those offered for the smart city.…”
Section: B the Owc-iott In Smart Citiesmentioning
confidence: 99%
“…The main challenge is light's limited coverage, primarily when implemented in large warehouses with high ceilings [256]. Also, the pollution existing in industrial environments can degrade the performance of VLC systems [257]. The industrial VLC-based solutions reported in the literature are limited compared to those offered for the smart city.…”
Section: B the Owc-iott In Smart Citiesmentioning
confidence: 99%
“…The dimensions, irregular forms of these suspended particles with time-variable of cloud-density, negatively influence the entire VLC system, and consequently, the magnitude of optical power that hits the photodetector’s active area continuously changes. The extinction coefficient ( k ), due to many time-variable parameters underground, cannot be accurately calculated according to equation [ 98 ]: where: λ —wavelength; I r —intensity of light at destination; I i —intensity of light at source; t —medium thickness.…”
Section: The Proposed Underground Ptandms With Hybrid (Rf/vlc) Local-...mentioning
confidence: 99%
“…The extinction coefficient ( k ), due to many time-variable parameters underground, cannot be accurately calculated according to equation [ 98 ]:…”
Section: The Proposed Underground Ptandms With Hybrid (Rf/vlc) Local-...mentioning
confidence: 99%
“…The main challenge is light's limited coverage, primarily when implemented in large warehouses with high ceilings [241]. Also, the pollution existing in industrial environments can degrade the performance of VLC systems [242]. The industrial VLC-based solutions reported in the literature are limited compared to those offered for the smart city.…”
Section: B the Owc-iott In Smart Citiesmentioning
confidence: 99%